Muscle activity of Bulgarian squat. Effects of additional vibration, suspension and unstable surface - Aguilera-Castells, J.; Buscà, B.; Morales, J.; Solana-Tramunt, M.; Fort-Vanmeerhaeghe, A.; Rey-Abella, F.; Bantulà, J.; Pena, J. (PLOS ONE, 2019)
Practitioners of strength and conditioning are increasingly using vibration and unstable environments to enhance training effects. However, little evidence has been found comparing the use of suspension devices and vibratory platforms used in the Bulgarian squat. The purpose of this cross-sectional study was to examine the effect of suspension devices (TRX®), unstable surfaces (BOSU®), and vibration plates on muscle activity and force during the Bulgarian squat. Twenty physically active male students (age = 24.40 ± 3.63 years) performed a set of five repetitions of Bulgarian squats, suspended lunges, suspended lunges-BOSU, suspended lunges-Vibro30, and suspended lunges-Vibro40 (vibration 30 Hz or 40 Hz and 4 mm of amplitude). A randomized within-subject design was used to compare leg muscle activity, vertical ground reaction forces, and force exerted on the strap across the five exercises. Results showed no significant differences in muscle activity between the Bulgarian squat and suspended lunge (p = 0.109, d = 2.84). However, the suspended lunge significantly decreased muscle activation compared to the suspended lunge-BOSU (p = 0.012, d = 0.47), suspended lunge-Vibro30 (p = 0.001, d = 1.26), and suspended lunge-Vibro40 (p = 0.000, d = 1.51). Likewise, the Bulgarian squat achieved lower activity than the suspended lunge-Vibro40 (p = 0.010, d = 0.96). The force on the strap significantly decreased in the suspended lunge-BOSU compared to the suspended lunge-Vibro30 (p = 0.009, d = 0.56). The suspended lunge achieved higher front leg force production than the Bulgarian squat (p = 0.006, d = 0.48). In conclusion, leaning the rear leg on a suspension device does not provoke an increase in the activation of the front leg during the Bulgarian squat but increases the vertical ground reaction forces. Thus, the use of unstable surfaces or vibration plates for the front leg increased muscular activity when performing a suspended lunge.